The Mechanical Properties and Corrosion Behavior of Quaternary Mg-6Zn-0.8Mn-xCa Alloys - Bakhsheshi-Rad, Hamid Reza (Springer New York LLC, 2015)
In present study, the influence of calcium content on the microstructure, mechanical properties and corrosion behavior of quaternary Mg-6Zn-0.8Mn-xCa alloys, where x = 1, 1.5, 3 or 4.5 wt.% Ca, was examined. The grain structure of this quaternary alloy system became more refined with increasing additions of Ca. In addition to a-Mg, the Ca2Mg6Zn3 phase was found to be present in Mg-6Zn-0.8Mn-1Ca and Mg-6Zn-0.8Mn-1.5Ca according to microstructural and thermal analysis (TA). In addition to the a-Mg and Ca2Mg6Zn3 phases, the Mg2Ca phase was found to be present in the Mg-6Zn-0.8Mn-3Ca and Mg-6Zn-0.8Mn-4.5Ca alloys. Alloys with 1 or 1.5 wt.% Ca led to increases in the tensile strength of Mg-6Zn-0.8Mn, although further Ca additions had a deleterious effect. The TA of Mg-6Zn-0.8Mn-xCa during its solidification indicates that the fraction of liquid phase increases with increasing Ca content at the dendrite coherency point, leading to an increase in secondary phases and increased corrosion rate of Mg-6Zn-0.8Mn-xCa alloys.